EVERYDAY LIFE IN MEDIEVAL PORTUGAL. A HISTORIOGRAPHIC OVERVIEW - Coelho, Maria Helena da Cruz (2015)
This historiographic overview presented begins with a very early book written in the 1960s by Antonio Henrique de Oliveira Marques. A Sociedade Medieval Portuguesa. Aspectos da Vida Quotidiana (Portuguese Medieval Society. Aspects of Everyday Life) and ends with the collective work published in 2012, História da Vida Privada em Portugal (A History of Private Life in Portugal), the first volume of which focuses on the Middle Ages. We seek to chart a course between these two milestones, setting out developments in studies of economic, social, religious and cultural history and the history of mentalities that have dealt with aspects of everyday life: the home, the dining table and other forms of conviviality, in more rural or urban environments; work days and festive occasions; devotions, religiosity and death; and family, women and children.